2016
DOI: 10.1111/acer.12953
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the GABAA Receptor in Age‐Dependent Differences in Binge‐Like Ethanol Intake

Abstract: This study adds to the existing literature demonstrating the crucial role of the GABAA receptor in alcohol consumption. In addition, it suggests that age differences in the GABAA receptor modulation of binge alcohol drinking might be more dependent on extrasynaptic GABAA receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 52 publications
(65 reference statements)
2
14
0
Order By: Relevance
“…Previous studies from our lab (Moore et al, 2007; Fritz and Boehm, 2014; Quoilin and Boehm, 2016) and others (Ramaker et al, 2011, 2012, 2014a, 2014b) have shown that THIP can significantly reduce voluntary ethanol consumption and operant responding for the drug. Given THIP’s high affinity for δ-GABA A Rs, these data support a possible role for these extrasynaptically located GABA A receptors in mediating this pattern of ethanol use.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Previous studies from our lab (Moore et al, 2007; Fritz and Boehm, 2014; Quoilin and Boehm, 2016) and others (Ramaker et al, 2011, 2012, 2014a, 2014b) have shown that THIP can significantly reduce voluntary ethanol consumption and operant responding for the drug. Given THIP’s high affinity for δ-GABA A Rs, these data support a possible role for these extrasynaptically located GABA A receptors in mediating this pattern of ethanol use.…”
Section: Discussionmentioning
confidence: 68%
“…Indeed, genetic inactivation of δ-GABA A R in the nucleus accumbens reduces alcohol-drinking behavior in male mice (Nie et al, 2011). Further, pharmacological manipulation using 4,5,6,7-tetrahydroisoxazolo[5,4-c]pyridine-3-ol (THIP/gaboxadol), an agonist with high efficacy and selectivity for δGABA A Rs (Boehm et al, 2006; Bhattarai, 2011; Meera, 2011; Mortensen 2010), reduces binge alcohol consumption in mice (Moore et al, 2007; Fritz and Boehm, 2014; Quoilin and Boehm, 2016). However, no study has explored the effect that estrous cycle may have on the role that δ-GABA A Rs play in mediating binge drinking in females.…”
Section: Introductionmentioning
confidence: 99%
“…It is also noteworthy that adolescent rats are initially less sensitive to ethanol-induced sleep disruption (Ehlers et al, 2013). Thus, it is conceivable that the initial lack of circadian- and sleep-related consequences adolescent rodents experience with acute ethanol may contribute to their higher alcohol consumption (Holstein et al, 2011, Melendez, 2011, Moore et al, 2010, Quoilin and Boehm, 2016). However, given that adolescent rats also show greater slow wave sleep suppression the day following acute ethanol compared to adults (Ehlers et al, 2013), it is also tempting to speculate that heavy drinking in adolescents may be reinforced during hangover to induce sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Results from studies employing C57BL/6J mice are somewhat more variable, although generally comparable to those in rats. During adolescence, mice of this strain consume more alcohol than adults, particularly in models of limited access, intermittent access, and binge-drinking (Holstein et al, 2011, Melendez, 2011, Moore et al, 2010, Quoilin and Boehm, 2016; but see also Hefner and Holmes, 2007). Adolescent C57BL/6J mice also show differential sensitivity to acute ethanol, including increased sensitivity to ethanol-induced locomotor stimulation (Hefner and Holmes, 2007, Melon and Boehm, 2011), anxiolysis (Hefner and Holmes, 2007), and certain memory impairments (Lacaille et al, 2015, Spanos et al, 2012), and decreased sensitivity to ethanol-induced conditioned taste aversion (CTA; (Holstein et al, 2011, Moore et al, 2013), sedation (Hefner and Holmes, 2007, Linsenbardt et al, 2009), hypothermia and locomotor suppression (Lopez et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…As a positive control, we also assessed the effects of the non-selective GABA A agonist muscimol, which has been previously shown to potentiate the sedative effects of ethanol (Holstein et al, 2004). We selected doses of pBBG and Muscimol that had been previously shown to inhibit ethanol drinking (McMurray et al, 2017a;Quoilin & Boehm, 2016). To further explore whether GLO1 alterations affect the locomotor response to ethanol, we also assessed the effect of Glo1 overexpression on the locomotor response to ethanol.…”
Section: Introductionmentioning
confidence: 99%